Enhancement of air-stability, π-stacking ability, and charge transport properties of fluoroalkyl side chain engineered n-type naphthalene tetracarboxylic diimide compounds - Gogoi, Gautomi; Bhattacharya, Labanya; Sahoo, Smruti R; Sahu, Sridhar; Sarma, Neelotpal Sen; Sharma, Sagar (RSC advances, 2021)
In this study, the impact of fluoroalkyl side chain substitution on the air-stability, π-stacking ability, and charge transport properties of the versatile acceptor moiety naphthalene tetracarboxylic diimide (NDI) has been explored. A density functional theory (DFT) study has been carried out for a series of 24 compounds having different side chains (alkyl, fluoroalkyl) through the imide nitrogen position of NDI moiety. The fluoroalkyl side chain engineered NDI compounds have much deeper highest occupied molecular orbitals (HOMO) and lowest unoccupied molecular orbitals (LUMO) than those of their alkyl substituted compounds due to the electron withdrawing nature of fluoroalkyl groups. The higher electron affinity (EA > 2.8 eV) and low-lying LUMO levels (<−4.00 eV) for fluoroalkyl substituted NDIs reveal that they may exhibit better air-stability with superior n-type character. The computed optical absorption spectra (∼386 nm) for all the investigated NDIs using time-dependent DFT (TD-DFT) lie in the ultra-violet (UV) region of the solar spectrum. In addition, the low value of the LOLIPOP (Localized Orbital Locator Integrated Pi Over Plane) index for fluoroalkyl side chain comprising NDI compounds indicates better π-π stacking ability. This is also in good agreement for the predicted π-π stacking interaction obtained from a molecular electrostatic potential energy surface (ESP) study. The π-π stacking is thought to be of cofacial interaction for the fluoroalkyl substituted compounds and herringbone interaction for the alkyl substituted compounds. The calculated results shed light on why side chain engineering with fluoroalkyl groups can effectively lead to better air-stability, π-stacking ability and improved charge transport properties. In this study, the impact of fluoroalkyl side chain substitution on the air-stability, π-stacking ability, and charge transport properties of the versatile acceptor moiety naphthalene tetracarboxylic diimide (NDI) has been explored.